Walt Disney's Snow White and the seven dwarfs. - Walt Disney Company (Danbury, Conn. : Grolier Enterprises, 1994)
Retells the Grimm story in which a princess escapes her murderous stepmother by hiding out in the home of seven hospitable dwarfs.
"Originally published in Denmark as Snehvide og de syv dvaerge by Egmont Books, Copenhagen, in 1994."--T.p. verso.
Keywords: Fairy tales; Folklore -- Germany -- Juvenile literature